Penilaian Terhadap Alat Medis dan Non-Medis di Praktik Mandiri Bidan - Galuh Nugraheni; Astri Nurdiana (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Independent Midwifery Practice (IMP) is a community medical facility authorized to provide midwifery practice, including maternal, neonatal, reproductive health, and contraceptive services. The operation of IMP is regulated by Regulation of the Ministry of Health, the Republic of Indonesia No. 28 of 2017, about midwifery practice standards. However, the assessment of the operations of IMP has not been conducted yet. This study aims to assess IMP in Karawang district using assessment forms according to the Regulation of the Ministry of Health of the Republic of Indonesia No 28 of 2017. This study was conducted at 53 teaching IMPs in Karawang District from July to November 2018. This study uses a mixed-method with a sequential explanatory design. The findings show that the tools, drugs, and other medical consumables are not entirely available at the IMPs. The Obgyn toolset, family planning toolset, vaccinations toolset, and resuscitation toolset were not complete. Providing mandatory sources at the IMPs is very important to support the provision of quality. It is required to optimize the monitoring and evaluation activity by the authorized institution.